The Engine Performance Characteristics of an IDI Diesel Engine Fueled by Soybean Oil Methyl Esters - Ghurri, A; Keun, S K (Journal of Engineering and Scientific Research, 2019)
An experimental investigation was conducted to evaluate the performance of anindirect injection (IDI) diesel engine using diesel (D100) and diesel-biodieselblends (BD25, BD45, BD65) separately. The engine was run in various engineloads at constant engine speed ranging from 1000 to 2400 rpm with an interval200 rpm. The results showed that the biodiesel content decreased the enginetorque and power. This might be mainly affected by the lower LHV of thebiodiesel, and also the worse combustion due to higher density of the biodieselcompared to the diesel fuel. The loss of power due to lower heating value ofbiodiesel were not as high as the difference in their heating value that might bedown to the better lubricity of biodiesel as proved in the higher brake thermalefficiency and mechanical efficiency when using the biodiesel blends. The brakespecific fuel consumption is higher with the increase of biodiesel content but thediesel fuel delivered the highest energy to run the engine. The maximum pressureinside cylinder and the heat release rate of D100 is slightly higher than those ofbiodiesel blends.Keywords: diesel engine, biodiesel, engine performance, emission.